ECONOMIC GROWTH, WORK OPPORTUNITY AND EDUCATION POLICY - ., Soedjanarto (International Business Education Journal, 2008)
This economic growth was the result of economic development that create increasing output from each input both fact input of natural production, capital and skilled labor. The growth of input aggregately will create revenue of aggregate consumption and finally will open work opportunity. Economic growth include national growth, sector growth and competition growth. Therefore, it needed the planning and education policy with approach such as: social demand approach, needs for national approach and development generation approach. Especially for high education it was necessary to emphasize on preparation because of nation leadership and mastering the development of science and technology in the future. One effort that can be done was by represhing leadership insight and superiority.